2007
DOI: 10.1017/s0269888907001166
|View full text |Cite
|
Sign up to set email alerts
|

Adding deductive logic to a COTS spreadsheet

Abstract: We exploit the spreadsheet metaphor to make deductive problem-solving methods available to the vast population of spreadsheet end users. In particular, we show how the function-based problem-solving capabilities of spreadsheets can be extended to include logical deductive methods in a way that is consistent with the existing spreadsheet "look and feel." The foundation of our approach is the integration of a standard deductive logic system into a successful Commercial-Off-The-Shelf (COTS) spreadsheet. We have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…In 2004 DARPA (Defense Advanced Research Projects Agency, EUA) promoted an event (Small Business Innovation Research) in which several deductive spreadsheet have been presented. As a consequence, four projects appeared: NEXCEL [Cervesato, 2007], LESS [Valente et al, 2007], XcelLog [Ramaskrishnan et al, 2007] and [Tallis et al, 2007]. All those systems aimed to enrich Microsoft Excel features.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004 DARPA (Defense Advanced Research Projects Agency, EUA) promoted an event (Small Business Innovation Research) in which several deductive spreadsheet have been presented. As a consequence, four projects appeared: NEXCEL [Cervesato, 2007], LESS [Valente et al, 2007], XcelLog [Ramaskrishnan et al, 2007] and [Tallis et al, 2007]. All those systems aimed to enrich Microsoft Excel features.…”
Section: Related Workmentioning
confidence: 99%
“…In [Tallis et al, 2007] a different approach is proposed, this one using, alternatively, Prolog, Jess (a rule engine that implements the Rete algorithm), or KAON2 (an inference engine that manages Ontologies). We have not found any example or application of this approach, but according to authors, one of its major strengths is the ability to use a semantic representation (OWL, for instance) of the knowledge base.…”
Section: Related Workmentioning
confidence: 99%
“…Research has shown that spreadsheets are a form of code, with spreadsheet users acting as end-user programmers [2]. Excel, specifically, remains one of the most popular end-user programming environments, with its importance in the business world continuing to rise [3]. Microsoft's recent announcement of Python integration within Excel signifies a major step towards enhanced data analysis capabilities within familiar software environments.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a system that extends the spreadsheet paradigm with deductive reasoning capabilities [5], [6]. This system extended Microsoft Excel with the OWL and SWRL logic formalism [7], [8].…”
Section: Introductionmentioning
confidence: 99%